Using VISIR in a large undergraduate course: preliminary assessment results - Alves, Gustavo R. (2014)
The use of remote labs in undergraduate courses has been reported in literature several times since the mid 90's. Nevertheless, very few articles present results about the learning gains obtained by students using them, especially with a large number of students, thus suggesting a lack of data concerning their pedagogical effectiveness. This paper addresses such a gap by presenting some preliminary results concerning the use of a remote laboratory, known as VISIR, in a large undergraduate course on Applied Physics, with over 500 students enrolled.